Surgical Technique for Open Reduction–Internal Fixation of an Unstable Displaced 3-Part Proximal Humeral Fracture Using a Proximal Humeral Locking Plate - Kanchanatawan, Wichan (Arthrosc Tech, 2017)
The proximal humeral locking plate (PHLP) is a recently developed fixed-angle implant that is an option for open reduction–internal fixation of an unstable displaced proximal humeral fracture. Various articles have reported successful outcomes using the PHLP when compared with other implant designs. However, many complications still occur with use of the PHLP, such as avascular necrosis of the humeral articular fragment, malreduction (particularly varus malalignment), and screw penetration. These complications are related to the difficulty in fixation of this particular type of fracture, as well as ineffective surgical technique. We have therefore proposed a step-by-step surgical technique for open reduction–internal fixation of an unstable displaced 3-part proximal humeral fracture using a PHLP. This technique focuses on the precise placement of the PHLP according to the plate design, as well as an effective intraoperative assessment, to improve surgical outcomes and prevent the various complications of proximal humeral fractures.